IDEOLOGY AND LINGUISTIC LEVEL EQUIVALENCE FOR THE TRANSLATION OF THE MOVIE SUBTITLE OF “GUARDIANS OF THE GALAXY” - Nur Laili yusuf Yusuf (Mastery: Master of English Language Journal, 2023)
This study aims to investigate the equivalence in translation of movie subtitle at the linguistic level and its ideology. The data were taken from the movie script entitled “Guardians of the Galaxy” in English and its Indonesian subtitles. This study was conducted based on qualitative research methods with the descriptive analysis. The results of the analysis showed that there were found 51 data for equivalence at word level, 37 data for equivalence at above word level, 224 data for grammatical equivalence, 101 data for textual level, 29 data for pragmatic level equivalence In addition, there were found 30 data for foreignization ideology and 15 data for domestication ideology. In the end, it turns out that much of the information is equivalent on a grammatical level, and most of the translations made use of foreignization ideology to preserve the original language's culture. Although grammatical equivalency is frequently used in foreignization ideology, it is not always employed. Since grammar plays such a pivotal role in translation, linguistic equivalent at all levels—from the word to the text to the pragmatic— must be based on grammatical equivalence.